2018
DOI: 10.1167/18.13.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparing set summary statistics and outlier pop out in vision

Abstract: Visual scenes are too complex to perceive immediately in all their details. Two strategies (among others) have been suggested as providing shortcuts for evaluating scene gist before its details: (a) Scene summary statistics provide average values that often suffice for judging sets of objects and acting in their environment. Set summary perception spans simple/complex dimensions (circle size, face emotion), various statistics (mean, variance, range), and separate statistics for discernible sets. (b) Related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 42 publications
4
40
0
Order By: Relevance
“…Hansmann-Roth et al (2019) found that while observers were sensitive to differences in mean color, and in variance, they were not able to visually detect any differences when the two arrays differ only in terms of the shape of the underlying colour distribution. These findings agree with other findings (Hochstein et al 2018), as well as Rahnev's view on perceptual decisions. When faced with a perceptual decision (i.e.…”
Section: Perception Versus Perceptual Decisionsupporting
confidence: 94%
See 1 more Smart Citation
“…Hansmann-Roth et al (2019) found that while observers were sensitive to differences in mean color, and in variance, they were not able to visually detect any differences when the two arrays differ only in terms of the shape of the underlying colour distribution. These findings agree with other findings (Hochstein et al 2018), as well as Rahnev's view on perceptual decisions. When faced with a perceptual decision (i.e.…”
Section: Perception Versus Perceptual Decisionsupporting
confidence: 94%
“…There was remarkable correspondence in the CT-PD curves between the shape of the underlying representation of the distractor distribution and the shape of the physical distractor distribution. This correspondence is especially important given that the two different distractor distributions had the same mean and range, which are summary statistical variables crucial for outlier detection among a set of visual items (Hochstein, Pavlovskaya, Bonneh & Soroker, 2018). This indicates that the difference observed in the CT-PD curves (Figure 4) cannot be attributed to summary statistic representations.…”
Section: Resultsmentioning
confidence: 90%
“…Or is detailed information about feature distributions retained in some way? Information can be reduced to the mean and variance of a distribution and perceptual tasks like outlier detection or categorization can be performed through knowledge of the statistics (Hochstein et al, 2018;Khayat & Hochstein, 2018;Utochkin, 2015). However, optimal behaviour requires the encoding of a full feature probability distribution that is not always easy to summarize with simple statistics.…”
Section: Discussionmentioning
confidence: 99%
“…My lab turned to the field of set mean perception, showing that participants perceive both set mean and range, and that these are perceived automatically, implicitly (i.e., while consciously performing only a different task that is unrelated to set mean or range), and on-the-fly trial-by-trial (Khayat & Hochstein, 2018; see also Khayat & Hochstein, 2019). We also studied the relationship between set statistics perception and feature search pop out (Hochstein et al, 2018). We used similar experimental displays for these two tasks, asking participants to compare two arrays of variously oriented bars and report either which set was oriented more clockwise on average (mean perception) or which contained an outlier (feature pop-out).…”
Section: Set Summary Mean Perceptionmentioning
confidence: 99%
“…We found that mean perception depended only on the difference in orientation means of the two arrays and not on their orientation range. In contrast, outlier detection depended only on the distance of the outlier from the set range edge (in order that it be an outlier) and again not on the range itself (Hochstein et al, 2018).…”
Section: Set Summary Mean Perceptionmentioning
confidence: 99%